CP-115 Second generation direct acting antiviral agents in post-transplant hepatitis c virus infection recurrence: Real clinical practice. (14th February 2016) - Chamorro-De-Vega, E; Gomez-Marquez, AM; Gimenez-Manzorro, A; Romero-Jimenez, R; Rodriguez-Gonzalez, C; Martinez-Fernandez-Llamazares, C; Ibañez-Garcia, S; Tovar-Pozo, M; Herranz-Alonso, A; Sanjurjo-Saez, M
Abstract : Background: Patients who have recurrent hepatitis C virus (HCV) infection after liver transplantation (LT) have substantial rates of morbidity and mortality. Evaluation of experience with new drug regimens is critical. Purpose: The aim was to describe the effectiveness and safety of second generation direct acting antivirals (DAAs) in patients with HCV recurrence after the LT regimen became critical. Material and methods: Descriptive, retrospective, non-interventional study. Inclusion criteria: all HCV monoinfected patients with LT who started treatment with DAAs before April 2015. The following variables were collected from the digital medical record: demographics, fibrosis degree, clinical data (decompensated cirrhosis, hepatocellular carcinoma), response to previous HCV treatment, viral genotype, viral load and analytical data (at baseline and at the end of treatment), and adverse events (AEs). Primary effectiveness endpoint was sustained virologic response 12 weeks after the end of treatment (SVR12). Secondary endpoint was end of treatment virologic response (EOTVR) and normalisation of serum transaminases at the end of treatment. Safety was evaluated by laboratory abnormalities and AEs. Results: 22 patients were included: 21 (95.4%) were male; average age was 60 (SD 7.4) years. There were 18 (81.8%) cirrhotic patients, 11 (61.1%) of these were decompensated and 5 (22.7%) had hepatocellular carcinoma. 9 (40.9%) patients were treatment naïve, 9 (40.9%) had failed prior therapy with peginterferon/ribavirin and 4 (18.2%) had failed protease inhibitor. Distribution of virus genotypes were: 1a=3 (13.6%); 1b=17 (77.3%); 1 unknown=1 (2.3%); and 3=1 (2.3%). The prescribed DDAs were: sofosbovir+daclatasvir=10 (45.4%), sofosbuvir+simeprevir=7 (31.8%), sofosbuvir=3 (13.6%) and daclatasvir+simeprevir=2 (9.1%). Ribavirin was present in 14 (63.6%) patients' treatment. Treatment duration was 12 weeks in 10 (45.4%) patients and 24 weeks in 12 (54.5%). SVR12 was achieved in 16 (80.0%) patients (data available in 90.9%). EOTVR was achieved in 100% of patients (data available in 90.9%) and 77.8% of patients had normalised serum transaminases at the end of treatment (data available in 81.8%). Most frequent AEs were: asthenia 10 (45.4%), pruritus 8 (36.4%), confusion 6 (23.3%), dry skin 5 (22.7%), insomnia 5 (22.7%), headache 5 (22.7%), reduced appetite 5 (22.7%) and ribavirin associated anaemia 4 (66.7%). Conclusion: Our data showed that DAAs are effective, inducing a high SVR12 and improving hepatic function in this special population. Despite the incidence of AEs, there were no treatment discontinuations due to AEs. Most were acceptable and consistent with the disease status. References and/or Acknowledgements: Viruses 2015;7:5155-68 No conflict of interest.